STUDI PERBANDINGAN PENGURANGAN HARMONIK PADA BEBAN LAMPU HEMAT ENERGI DENGAN FILTER PASIF - Farid Alwan; Sapto Nisworo; Agung Trihasto (Wahana Ilmuwan, 2016)
The increase of amount used non linear loads could make a harmonic distortion at higher power. One of the non-linear load is the energy-saving lamps. Harmonic distortion has a negative effects that affect to operated an energy saving lamps. To reduce harmonics then used the passive filter as alternative to reduce harmonic.Filter is one of solution to way reduce harmonics. The results from installation of passive filters can produce THDi at single tuned filter amount of 53.62% for lamp 7 watt, 55.35% for lamp 11 watt and 55.46% for lamp 18 watt, and then the percentage could be tuned harmonic filter amounted is 4.66% for the lamp 7 watt, 5.16% for 11-watt bulbs, and 4.76% for a 18 watt lamp, for used of high pass filter orde 2 amounted is 47.39% for the lamp 7 watt, 51, 15% for a lamp 11 watt and 53.76% for lamp 18 watt, thus the percentage of harmonic tuned by the filter is 27.37% for the lamp 7 watt, 12.04% for 11-watt bulbs, and 7.68% for 18 watt lamp, for the used of Ctype filter amounted of 45.53% for the lamp 7 watt, 49.37% for 11 watt lamp and 56.73% for 18 watt lamp, thus the percentage of harmonic could tuned by the filter is 19,44% for the lamp 7 watt, 15.10% for 11-watt bulbs, and 2.58% for 18-watt bulbs.